Marketing Mix Strategy On The Purchase Decision Of Kuritos Crackers - Rita Feni; Anton Feriady; Indah Ayu Lestari; Elni Mutmainnah; Maheran Mulyadi; Jon Yawahar; Edy Marwan (AGRITEPA: Jurnal Ilmu dan Teknologi Pertanian, 2025)
Purpose: This study aims to analyze the impact of marketing strategies on consumer decisions in purchasing octopus cracker products produced by Kuritos Home Business in Linau Village, Kaur Regency. Methodology: The method used is a quantitative approach with a nonprobability sampling technique. Data were collected through questionnaires distributed to 100 respondents, and analyzed using multiple linear regression. Results: The results show that the variables price (t = 7.106), place (2.455), promotion (3.918), process (4.386), and physical evidence (2.492) have a significant effect on purchasing decisions. Meanwhile, the product (-0.269) and people/employees (-0.189) variables do not show a significant effect. The calculated F value of 59.906 and R² of 0.806 indicate a high predictive power of the model. Findings: The main findings indicate that of the seven marketing mix elements, five have a significant effect, with price as the most dominant factor. This study presents novelty by highlighting local products based on marine products in the context of marketing in household businesses in coastal areas. Novelty: This study presents novelty by highlighting local products based on marine products in the context of marketing in household businesses in coastal areas. Originality: The uniqueness of this study lies in its focus on micro-businesses based on regional specialties that are still rarely studied and a comprehensive approach in examining marketing elements towards consumer decisions. Conclusion: Marketing strategy is very important in influencing purchasing decisions. Kuritos is advised to focus on elements that have been proven to have an effect on increasing sales. Type of Paper : Empirical research article.